2021
DOI: 10.1111/birt.12566
|View full text |Cite
|
Sign up to set email alerts
|

The design of “TeamBirth”: A care process to improve communication and teamwork during labor

Abstract: Background: Despite evidence that communication and teamwork are critical to patient safety, few care processes have been intentionally designed for this purpose in labor and delivery. The purpose of this project was to design an intrapartum care process that aims to improve communication and teamwork between clinicians and patients. Methods: We followed the "Double-Diamond" design method with four sequential steps: Discover, Define, Develop, and Deliver. In Discover, we searched professional guidelines and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The planning board is a dry erase board present in every labor room that structures essential information, which includes the names of the full care team, the birthing person's preferences, care plans, and expectations for when the team will come together again (Appendix S1). 32 Huddles are structured full care team meetings that occur in the birthing person's room at key moments throughout labor, but most importantly on admission, when the care plan is discussed before clinical decision‐making. The number of huddles each birthing person experiences is determined by their course of labor.…”
Section: Introductionmentioning
confidence: 99%
“…The planning board is a dry erase board present in every labor room that structures essential information, which includes the names of the full care team, the birthing person's preferences, care plans, and expectations for when the team will come together again (Appendix S1). 32 Huddles are structured full care team meetings that occur in the birthing person's room at key moments throughout labor, but most importantly on admission, when the care plan is discussed before clinical decision‐making. The number of huddles each birthing person experiences is determined by their course of labor.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Misclassification worsened with age with the worst being among people older than 40 years. 3,4 To address this, the authors used a set of confirmed maternal deaths to reexamine age-related instances of maternal mortality in the United States and identify the leading causes of death. 5 As a result of issues with the pregnancy checkbox, the authors recoded data so that only death certificates where pregnancy or the postpartum were written in (vs only in a checkbox) were coded as having maternal causes for death.…”
mentioning
confidence: 99%
“…The third article offers a possible solution for making clinical decisions in a manner that prioritizes patient preference. 3 All of these articles share an interest in cesarean birth as an outcome.…”
mentioning
confidence: 99%
See 2 more Smart Citations